A COMPLEX RATING ASSESSMENT OF THE FINANCIAL POSITION OF RUSSIAN AGRICULTURAL ENTERPRISES:: METHODOLOGICAL ASPECTS - V. Moshchenko, Oksana; V. Smetanko, Aleksandr; I. Kruglyak, Ludmila; V. Romanova, Svetlana; A. Maryanova, Svetlana (Gênero & Direito, 2020)
The article explores the problems of choosing the key indicators for quantitative assessment of financial state of companies. The methodological aspects of this assessment are examined using the example of agricultural industry. The purpose of the study is to prove the lack of a unified methodology for comparative assessment of financial and economic activities of business entities, taking into account current business conditions and industry specifics. The objectives of the study are to develop a unified methodology for assessing business situation based on nine key indicators provided by the SPARK-INTERFAX system. The economic content of key indicators of rating assessment based on SPARK-INTERFAX system was revealed in detail. The dynamics of sectoral average indicators of pig farms over the past 8 years have been shown. Using statistical methods, it was proved that reference of some key indicators can vary between sub-industries: pig breeding, poultry farming, etc. Therefore, a rating methodology has been developed to evaluate the financial position of enterprises, taking into account industry average values, controlled for the regional level. The practical significance of the study was tested at the three largest Russian pig breeding enterprises with the revenue of more than 10,000 million rubles.